Environmental & architectural phenomenology. Vol. 27, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 2016)
Vol. 27, No. 2, Summer/Fall 2016 (includes “citations received,” a book review of Peter L. Laurence’s Becoming Jane Jacobs, and essays by Tarek Wagih, Paul Krafel, Stephen Wood, and John Cameron)
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals